Development of a popular scientific book on briquette processing from palm oil empty fruit bunch waste as an alternative energy source - Istiqamah Istiqamah; Zahratunnisa Rahmadina (HAFECS PRESS, 2024)
The development of oil palm plantations, especially in Kalimantan, is increasing, this also increases plantation waste such as oil palm empty fruit bunch waste. This empty bunch waste has not been processed and utilised so that it continues to accumulate. One of the products that can be utilised from this empty bunch waste is briquettes as alternative energy. Besides being easy to process, it can also improve the community's economy and reduce empty bunch waste. This research aims to develop a book in the form of a popular scientific book on the processing of briquettes from oil palm empty fruit bunch waste as alternative energy. This research uses the Educational Design Research (EDR) type consisting of three stages, namely preliminary research, prototyping phase, and assessment phase. However, this study only limits the use to the prototype development phase. This research approach is quantitative and qualitative. The data in this study were described and analysed and then made into a popular scientific book. After that, the popular scientific book was evaluated using Tessmer formative evaluation design including self-evaluation, expert review and limited to one-to-one evaluation. The results of this study showed that the average final result of expert test validation of popular scientific book was 90.84% (very valid) and could be used without revision. The average final result of readability validation with a one-to-one evaluation of 83.33% (very valid) can be used as a reference source for a wide audience. Abstrak Perkembangan perkebunan sawit khususnya di Kalimantan begitu meningkat, hal ini juga meningkatkannya limbah perkebunan seperti limbah tandan kosong kelapa sawit. Limbah tandan kosong ini belum diolah dan dimanfaatkan sehingga terus menumpuk. Salah satu produk yang dapat dimanfaatkan dari limbah tandan kosong ini adalah briket sebagai energi alternatif. Selain mudah diolah, dapat pula meningkatkan perekonomian masyarakat dan mengurangi limbah tandan kosong. Penelitian ini bertujuan untuk mengembangkan buku berupa buku ilmiah populer mengenai pengolahan briket dari limbah tandan kosong kelapa sawit sebagai energi alternatif. Penelitian ini menggunakan jenis Educational Design Research (EDR) terdiri dari tiga tahapan, yaitu penelitian pendahuluan (preliminary research), tahap pengembangan prototipe (prototyping phase), dan tahap penilaian (assessment phase). Namun, penelitian ini hanya membatasi penggunaan hingga tahap pengembangan prototipe saja. Pendekatan penelitian ini yaitu pendekatan kuantitatif dan kualitatif. Data pada penelitian ini dijabarkan dan dianalisis kemudian dibuat menjadi sebuah buku ilmiah populer. Setelah itu, buku ilmiah populer dievaluasi dengan desain evaluasi formatif Tessmer meliputi evaluasi diri (self-evaluation), uji pakar (expert review) dan dibatasi sampai evaluasi perorangan (one to one evaluation). Hasil penelitian ini diketahui bahwa Rata-rata hasil akhir validasi uji pakar buku ilmiah populer diperoleh sebesar 90,84% (sangat valid) dan dapat digunakan tanpa revisi. Rata-rata hasil akhir validasi keterbacaan dengan evaluasi perorangan sebesar 83,33% (sangat valid) bisa digunakan sebagai sumber referensi khalayak luas.